Perbandingan Kinerja Keuangan Perbankan Syariah dan Konvensional: Studi Komparatif Berbasis Data Sekunder di Indonesia - Rika Indayanti; Ahmad Lutfi Rijalul Fikri; Muzakkir S. (Prodi Hukum Ekonomi Syariah (Muamalah), 2026)
This study aims to analyze and compare the financial performance of Islamic banks (BUS) and conventional banks (BUK) in Indonesia during the 2018–2023 period, focusing on profitability, operational efficiency, credit risk management, capital adequacy, and liquidity. This research employs a quantitative comparative method using secondary data analysis sourced from OJK's Sharia Banking Statistics (SPS) and Indonesia Banking Statistics (SPI) across multiple editions, as well as related academic literature. The sample consists of 10 Islamic Commercial Banks and 10 Conventional Commercial Banks with the highest total assets, selected through purposive sampling. Data were analyzed using descriptive statistics and comparative analysis based on key financial ratios. The results indicate that conventional banks outperform Islamic banks across all dimensions studied during the overall 2018–2023 period: ROA averaged 2.20% vs. 1.69%, BOPO 79.82% vs. 83.64%, NPL/NPF 2.73% vs. 2.92%, and CAR 24.84% vs. 21.67%. However, a significant finding is the marked improvement in Islamic bank performance following the merger forming Bank Syariah Indonesia (BSI) in 2021. In the 2022–2023 sub-period, Islamic banks recorded lower NPF (2.27%–2.42%) than the NPL of conventional banks (2.49%–2.78%), and achieved their best-ever BOPO of 77.28% in 2022, surpassing conventional banks